PENGARUH STRATEGI PEMBELAJARAN CARD SORT UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL (STUDI EKSEPERIMEN KUASI SISWA KELAS IV SD NEGERI 136 PEKANBARU) - Pratiwi, Citra; Marhadi, Hendri; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of student learning outcomes IPS. This is caused by the subject teachers do not use learning strategies in the learning process, so that students become bored, unfocused, and less attention to the teacher who was giving lessons. Based on this research by applying learning strategies Card Sort. The main objective of this study was to determine the effect of learning strategies Card Sort the learning outcomes of the fourth grade students of SD Negeri 136 Pekanbaru. This study will be conducted in two classes, and class IV.B IV.C IV.C where the class will be the experimental class and the class will be the class IV.B Control. The intensive research using about pretest and posttest to see the results of social studies students. Pretest is given before the learning process, as a matter of pretest is given then the learning process as much as three meetings in the experimental class and control class and only then given a posttest to determine the final outcome of the learning process. In this study, there is significant influence on the results of data analysis obtained 46% of the effect of learning strategies and the card sort test t where tcount> ttabel or 3.15> 1.996 so that Ho refused and Ha accepted. So it can be concluded that the hypothesis of action in accordance with the results of the study. In other words, there is a significant difference to the learning outcomes of students who acquire learning using learning strategy with a card sort who do not get treatment or conventional learning.Key Words: Card Sort, Learning Outcomes